Blood safety assessment of hepatitis A outbreak linked to frozen pomegranate arils: are foodborne outbreaks an emerging blood safety risk?. Issue 12 (23rd October 2019) - Styles, Claire E.; Hoad, Veronica C.; Kiely, Philip; Seed, Clive R.; Gosbell, Iain B.
Abstract : BACKGROUND: Foodborne hepatitis A virus (HAV) outbreaks are becoming more common in high‐income countries with low HAV incidence, and the associated blood safety risk may not be adequately mitigated by routine HAV risk mitigation strategies. This study describes the rapid risk modeling undertaken in response to a 2018 HAV outbreak in Australia associated with imported frozen pomegranate arils. STUDY DESIGN AND METHODS: The input parameters used in the modeling were the outbreak‐associated HAV incidence, duration of viremia, population seroprevalence, and rate of symptomatic infection in adults. The number and risk of viremic components issued, cases of transfusion transmission, and symptomatic infections among recipients were estimated. RESULTS: The incidence of pomegranate‐associated HAV infection among donors was very low, with fewer than 0.1 viremic fresh components estimated to have been released during the risk period. The risk of this event was less than one in 500, 000, and the risks of transfusion transmission and symptomatic illness in recipients were less than one in one million. When considering only donors who had consumed the pomegranate product, the risk was much higher, with approximately one in 1000 components estimated to be viremic. CONCLUSION: Rapid risk assessment indicated that the overall risk to blood safety associated with a small foodborne outbreak of HAV was negligible. Because fresh components collected from donors known to have consumed the affected product were at high risk, these donors were identified via signage in donor centers and deferred. The contribution of factors other than outbreak size to risk management decisions is discussed.